Blended Learning In English For Journalism - Abdul Syahid (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2019)
This study aims to investigate the effectiveness of Blended Learning in a community service of English for Journalism. To find out whether the journalists’ level of English proficiency after the training was better that that before the training, a single group of 15 female and 9 male journalists from 17 local and national media was given the blended learning of English for Journalism program four times a week in a total of 16 meetings of 120 minutes each. After such journalists’ needs as their level of English proficiency and having no fixed routine had been analyzed, community service was performed to help improve their English proficiency. Result shows that at the end of the training the 9 female and 15 male journalists achieved the Independent User B2 level which was higher than the Basic User A2 level at the beginning of the training. The result suggests that blended learning of English for Journalism community service was effective in improving the journalists’ English proficiency. It could also be adopted in the other branches of English for Specific Purposes, especially for busy working learners. The finding possibly provides useful direction for human resource managers, community service performers, and English language teachers.